The impact of climatic changes on the vegetation cover difference index in eastern Maysan governorate - MOhannad Tarish Qassem Al-Mazban (Journal of College of Education, 2023)
The researcher relied on the use of the most important modern and accurate indicators to determine the drought conditions that the region suffers from during the study period, the most important of which is the NDVI plant variation index, and in addition to that, remote sensing (RS) and(GIS) techniques were used, and by relying on satellite visuals to monitor and monitor all changes in vegetation cover, as it is one of the important indicators and indications of drought, which is the woman that reflects drought and its geographical distribution.
Keywords: climate change, vegetation cover difference index